Spanish dictionary : Spanish-English, English-Spanish revised and updated - Stern, Irwin; Succar, O. A; Weiman, Ralph William (New York Crown, 1993)
A beginning course for English speakers. Includes textbook, which covers grammar and dialogues, and a Spanish/English dictionary
Keywords: Conversation and phrase books; Spanish language; Dictionaries